1939
DOI: 10.1042/bj0330223
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine and the growth of Streptococcus haemolyticus

Abstract: IN the course of our analysis of the nutrients of Streptococcus haemolyticus it was found that growth did not take place in a mixture containing peptone,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1940
1940
1961
1961

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…McIlwain, Fildes, Gladstone & Knight (1939) showed that certain haemolytic streptococci were unable to grow in the absence of glutamine although glutamic acid is present. It is possible that glutamine (isoelectric point 5.56) passes the bacterial cell wall more easily than glutamic acid so the experiment was repeated with glutamine; the use of the decarboxylase preparation on boiled cells does not distinguish between glutamine and glutamic acid.…”
Section: Glutamic Acid and Glutaminementioning
confidence: 99%
“…McIlwain, Fildes, Gladstone & Knight (1939) showed that certain haemolytic streptococci were unable to grow in the absence of glutamine although glutamic acid is present. It is possible that glutamine (isoelectric point 5.56) passes the bacterial cell wall more easily than glutamic acid so the experiment was repeated with glutamine; the use of the decarboxylase preparation on boiled cells does not distinguish between glutamine and glutamic acid.…”
Section: Glutamic Acid and Glutaminementioning
confidence: 99%
“…McIlwain et al (220) reported that most strains of Streptococcus hemolyticus require glutamine for growth, and that the stimulating action of meat extract is due to its glutaniine content. Growth of the streptococci took place, though less actively, if glutamate ( a t a concentration 100 times greater) was supplied instead of glutamine (219).…”
Section: Glutamine As An Essential Growth Factormentioning
confidence: 99%
“…This concentration is about the same as the least concentration of biotin which is effective for yeast. Various strains of diphtheria bacilli (Mueller & Klotz, 1938), hemolytic streptococci (Subbarow & Rane, 1939;McIlwain, 1939; Woolley & Hutchings, 1939;Krauskopf et al 1939), and Proteus (Pelczar & Porter, 1940) also require pantothenic acid for growth. In the case of the lactic acid bacteria B-alanine cannot serve as a nutrilite.…”
Section: T H I S Was Obtained In (+)mentioning
confidence: 99%